2008
DOI: 10.1016/j.abb.2007.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic interactions in the denatured state ensemble: Their effect upon protein folding and protein stability

Abstract: It is now recognized that the denatured state ensemble (DSE) of proteins can contain significant amounts of structure, particularly under native conditions. Well-studied examples include small units of hydrogen bonded secondary structure, particularly helices or turns as well hydrophobic clusters. Other types of interactions are less well characterized and it has often been assumed that electrostatic interactions play at most a minor role in the DSE. However, recent studies have shown that both favorable and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 48 publications
2
62
1
Order By: Relevance
“…It is the ensemble of transient residual structure in the unfolded state that has been characterized in the case of ACBP; however, it seems most likely that many other unfolded proteins could be candidates for a similar study. The relatively simple approach, which has been used in this work, may also become a useful experimental technology for characterizing the unfolded states of proteins in other respects such as reengineering interaction sites (50, 51), or systematic studies of the effects of electrostatics on protein folding (52). The method is therefore seen to have a potential to become an important experimental tool for the advancement of our understanding of the protein folding problem.…”
Section: Resultsmentioning
confidence: 99%
“…It is the ensemble of transient residual structure in the unfolded state that has been characterized in the case of ACBP; however, it seems most likely that many other unfolded proteins could be candidates for a similar study. The relatively simple approach, which has been used in this work, may also become a useful experimental technology for characterizing the unfolded states of proteins in other respects such as reengineering interaction sites (50, 51), or systematic studies of the effects of electrostatics on protein folding (52). The method is therefore seen to have a potential to become an important experimental tool for the advancement of our understanding of the protein folding problem.…”
Section: Resultsmentioning
confidence: 99%
“…DSE electrostatic interactions have been detected in a range of proteins of diverse structure (30,(36)(37)(38)(39)(40)(41)(42), and there are examples of mutations that alter DSE energetics (43). There are also numerous examples in which mutation of charged surface residues leads to effects that differ in magnitude or even directionality from the expected results.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough thermodynamic analysis revealed that the main origin for the stabilization introduced by glycosylation is the unwinding of the residual native structure formed in the unfolded state, which results in a higher enthalpy. This effect serves as another indication of the importance of the unfolded state in controlling and shifting the thermodynamics and kinetics of protein folding (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%